UPAYA MENINGKATKAN KEMAMPUAN GURU DALAM PENGGUNAAN METODE PEMBELAJARAN MELALUI SUPERVISI KLINIS DI SDN 12 ALUR BANDUNG - ., Mahud (Jurnal Pembelajaran Prospektif, 2021)
The teacher's job is to diagnose learning needs, plan lessons, give presentations, ask questions, and evaluate teaching. Effective classroom management is a critical prerequisite for effective instructional activities so that a teacher can successfully manage the classroom, he should be able to anticipate student misbehavior and prevent such behavior from occurring. The schoolwith the title "Efforts to Improve Teacher Ability in Using Learning Methods Through Clinical Supervision at SD Negeri 12 Alur Bandung, Teluk Batang District, Kayong Utara Regency, 2019/2020 Academic Year". Improving the ability of teachers to use learning methods through clinical supervision is one solution that is quite effective. This can be seen from the final resultsof the study where teachers can master existing indicators in determining learning methods and look for methods that are truly appropriate and in accordance with learning objectives as well as the conditions of the classroom environment and the school environment itself which in turn provides benefits for improving student achievement. and improving school quality